Methods for Detecting Fake Profiles in Online Social Networks Using Artificial Neural Networks - Suresh, Dr. Koparthi; Prasad, Dr. RVVSV (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2020)
In light of the current situation, most individuals are participating in online social networks. Everyone, from kids to adults, spends a lot of time on these sites, either learning new things or getting in touch with friends and family in more effective ways. However, today's social media platforms are plagued by a large number of bogus accounts that exploit security flaws in order to steal from the sites or commit cybercrimes themselves.